Tax In Nusantara: Historical Analysis of The Fiscal Sociology Dynamics - Geby Febiola Lenggu; Ari Budi Kristanto (Perspektif Akuntansi, 2022)
This study aims to analyze the application of taxes in several civilizations in Nusantara by using fiscal sociology perspective. This study analyzes the background of tax collection and the use of the funds, by identifying the existence of Modernization, Elite, and Militaristic backgrounds as the elements of fiscal sociology view. The literatures of taxation history were analyzed to examine the research purpose. The research comprises the identification of the traditional, colonial, independence, as well as the modern period. The result shows that the tax collection in Nusantara differ time by time, in term of the fiscal sociology perspective. Tax collection with the Elite background occurred in the traditional period, namely during the Majapahit, Ancient Mataram, and Ancient Bali kingdoms. As for the Dutch, British and Japanese colonialism, there was a change in which taxes were collected based on the Elite and Militaristic reason. Furthermore, from the Indonesian independence until now, taxation is levied against the background of Modernization Dimension.